Peacemonger - Goulding, Marrack (London : J. Murray, 2002)
"Marrack Goulding joined the United Nations as the Under-Secretary-General in charge of Peacekeeping Operations in 1986, at a time of intense optimism. With the thawing of the Cold War it seemed that at last the UN could concentrate on the real issues affecting the world: preventing and resolving conflict, and fighting poverty, disease, injustice and crime. At first there were spectacular successes - the withdrawal of Soviet troops from Afghanistan, the Iran-Iraq ceasefire, the liberation of Kuwait, and peace settlements in Namibia, Angola, El Salvador, Cambodia and Mozambique. The UN, it seemed, could do no wrong. But by 1993 the bubble had burst, and the UN's credibility had been seriously undermined by its failure to halt the bloodshed in Angola, Bosnia and Somalia. Meantime, spending on peacekeeping had risen more than tenfold, from $260 million to $2.7 billion. In 1993 an exhausted Goulding was transferred by Secretary Boutros-Ghali to head the UN's political department." "In this account of seven years of peacekeeping, Marrack Goulding gives us a unique insider's view of what went wrong and also of what the UN achieved during this critical period, of UN peacekeeping activities, and also to work behind the scences with two very different Secretaries-General, Javier Perez de Cuellar and Boutros Boutros-Ghali. In this thought-provoking account of an organization in crisis he pulls no punches, but readily admits that 'many of the mistakes were my mistakes - I was as intoxicated as everyone else.'"--Jacket.
Includes bibliographical references (pages 351-364) and index.
Keywords: Goulding, Marrack; United Nations -- Officials and employees -- Biography; Nations Unies -- Forces de maintien de la paix; Geschichte 1986-1992; Employees; Peacekeeping forces; Biographies